Counter-hegemony of the East Java Biennale art community against the domination of hoax content reproduction - Jokhanan Kristiyono; Rachmah Ida; Musta'in Mashud (Masyarakat, Kebudayaan dan Politik, 2020)
This research analyses and describes in detail how the digital biennale activities that are a part of the Indonesian Digital art community has become a form of criticism and silent resistance to the social hegemony. It refers to the ideology, norms, rules, and myths that exist in modern society in Indonesia, especially the reproduction of hoax content. Hoax refers to the logic people who live in a world of cyber media with all of its social implications. This phenomenon is a problem, and it is at the heart of the exploration of the art community in East Java Biennale. The critical social theory perspective of Gramsci’s theory forms the basis of this research analysis. The qualitative research approach used a digital ethnomethodology research method focused on the online and offline social movements in the Biennale Art Community. The data collection techniques used were observation and non-active participation in the process of reproduction-related to the exhibition of Indonesian Biennale digital artworks. It was then analyzed using Gramsci’s hegemony theory. The purpose of this study was to describe the process of social movements in a digital format conducted by the Indonesian Biennale when reproducing works of art to counteract the dominance and hegemony of the Hoax phenomenon in Indonesia. The benefit of this research was that it obtained a preposition of Gramsci’s hegemony theory in the world of digital art as created by contemporary Indonesian Biennale artists. Digital technology has had a tremendous effect on the media industry, government, trade, informal industry sector, human resources, urban planning, services, disaster relief, health, education, religion, artistic and cultural expression, in addition to various other fields. The conclusion obtained from this research is that there is a formation of a new hegemony, a digital hegemony. This new hegemony is of particular concern for the digital artists in East Java Biennale. Through the digital format works, the artists also try to communicate their art as a form of silent resistance, protest, and criticism of the hegemony that occurs in society, referring to the ideology, norms, and myths. It can be called a digital counter-hegemony.s